Analisis Hukum Ekonomi Syariah terhadap Praktik Pengupahan Pekerja Pemanen Getah Damar dengan Sistem Harian Lepas - Fahmi Nur Rohman; Yusuf Baihaqi; Apriansyah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the wage system for daily resin tappers and examine its conformity with the principles of ujrah contract in Islamic economic law. This research employed a qualitative approach using field research conducted in Pekon Lemong, Lemong District, Pesisir Barat Regency. Data were collected through observation, interviews, and documentation, and analyzed descriptively by relating empirical findings to the concept of ujrah. The findings reveal that the wage system is implemented through verbal agreements based on mutual trust and local customary practices. Wage determination considers the level of work difficulty, the number of damar trees tapped, and the quantity of resin harvested. From the perspective of Islamic economic law, the practice fulfills the essential elements (arkan) of the ujrah contract, as it involves contracting parties, a clearly defined object of work, and wages as compensation for services rendered. However, the fulfillment of contractual requirements has not been fully achieved due to the lack of clarity regarding wage amounts, payment schedules, and wage deductions. These conditions indicate a potential element of gharar that may affect legal certainty and the protection of workers' rights. Nevertheless, the existing practice can be aligned with the principles of ujrah through greater transparency in wage determination and contract implementation without eliminating established community customs